The Role of MicroRNAs in Hyperlipidemia: From Pathogenesis to Therapeutical Application - Xiang, Yu; Mao, Li; Zuo, Mei-Ling; Song, Gui-Lin; Tan, Li-Ming; Yang, Zhong-Bao (Mediators of Inflammation, 2022)
Hyperlipidemia is a common metabolic disorder with high morbidity and mortality, which brings heavy burden on social. Understanding its pathogenesis and finding its potential therapeutic targets are the focus of current research in this field. In recent years, an increasing number of studies have proved that miRNAs play vital roles in regulating lipid metabolism and were considered as promising therapeutic targets for hyperlipidemia and related diseases. It is demonstrated that miR-191, miR-222, miR-224, miR-27a, miR-378a-3p, miR-140-5p, miR-483, and miR-520d-5p were closely associated with the pathogenesis of hyperlipidemia. In this review, we provide brief overviews about advances in miRNAs in hyperlipidemia and its potential clinical application value.